WAinar Graphic Design dengan Pendekatan Berbasis Komunikasi Digital untuk Meningkatkan Psikomotor Keterampilan Mahasiswa - Putu Gede Sukarata; I Gede Suputra Widharma (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
The development of technology is currently experiencing very rapid development. Technology in various areas of life is indispensable and very helpful for life itself. The existing example is the replacement of manual processes into digital processes, although not entirely replaceable. One example of a face-to-face learning process can be replaced with an online learning process, especially at this time of the Covid-19 pandemic that hit the world. In this study, researchers conducted an online learning process in the Graphic Design course using the whatsapp group media as a means of communicating with students. Learning Graphic Design courses are mostly done in practice. Researchers have conducted observations and experiments since March 2020. The presentation of the material carried out is with text, images and videos. In the communication process carried out using everyday languages ​​and interspersed with light jokes so that students do not experience boredom. The use of WhatsApp media was chosen considering its use is very familiar to students, besides that it is lighter and can be used at any time. The contents of the conversation on WhatsApp will be visible during the learning process or not. At the end of the lesson the researcher can see the results of the learning process and can be assessed well. In the next semester, the researcher redeveloped it by adding additional material through video tutorials uploaded to the youtube channel at the address http://youtube.com/c/GeTriRumahProduksi. The results obtained are better and closer to the expected results in the Graphic Design learning process. So from the researcher's assessment that learning through the whatsapp group media succeeded in improving the psychomotor in each student.